UJI BANDING BERBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN SELADA MERAH (Lactuca sativa var. crispa L) DENGAN MEDIA TANAM HIDROPONIK SISTEM NFT (Nutrient Film Technique) - G. F. Yanti; Ngadiani Ngadiani (FMIPA : Universitas PGRI Adi Buana, 2018)
A study has been conducted to compare some varieties of planting media on red lettuce (Lactuca sativa var crispa L), the variables observed in this study are wet weight and chlorophyll content. This research was conducted by using complete randomized design (RAL) consisting of 5 variants of planting medium (Rockwool (as control), cocopeat, fuel husk, cotton and sponge) with 4 replications. The results showed that rockwool planting media had significant effect (P <0,05) on wet weight of red lettuce plant (Lactuca sativa var. Crispa L). Then, on the results of chlorophyll content test, it was found that the variation of burning husk medium media on red lettuce plant had significant effect (P <0,05) to chlorophyll a and total chlorophyll, while in chlorophyll b the result obtained was not significantly different (P> 0, 05). The results of this study indicate that the treatment of rockwool planting media in red lettuce plant growth is effective to increase wet weight and the treatment of burning husk medium media can increase the chlorophyll content of red lettuce plants namely chlorophyll a and total chlorophyll red lettuce plants (Lactuca sativa var. Crispa L.). Keywords: red lettuce, wet weight, test of chlorophyll content a, chlorophyll b, total chlorophyll